Making patient blood management the new norm(al) as experienced by implementors in diverse countries - Axel Hofmann; Donat R. Spahn; Anke-Peggy Holtorf; PBM Implementation Group (BMC, 2021)
Abstract Background Patient blood management (PBM) describes a set of evidence-based practices to optimize medical and surgical patient outcomes by clinically managing and preserving a patient's own blood. This concepts aims to detect and treat anemia, minimize the risk for blood loss and the need for blood replacement for each patient through a coordinated multidisciplinary care process. In combination with blood loss, anemia is the main driver for transfusion and all three are independent risk factors for adverse outcomes including morbidity and mortality. Evidence demonstrates that PBM significantly improves outcomes and safety while reducing cost by macroeconomic magnitudes. Despite its huge potential to improve healthcare systems, PBM is not yet adopted broadly. The aim of this study is to analyze the collective experiences of a diverse group of PBM implementors across countries reflecting different healthcare contexts and to use these experiences to develop a guidance for initiating and orchestrating PBM implementation for stakeholders from diverse professional backgrounds. Methods Semi-structured interviews were conducted with 1-4 PBM implementors from 12 countries in Asia, Latin America, Australia, Central and Eastern Europe, the Middle East, and Africa. Responses reflecting the drivers, barriers, measures, and stakeholders regarding the implementation of PBM were summarized per country and underwent qualitative content analysis. Clustering the resulting implementation measures by levels of intervention for PBM implementation informed a PBM implementation framework. Results A set of PBM implementation measures were extracted from the interviews with the implementors. Most of these measures relate to one of six levels of implementation including government, healthcare providers, funding, research, training/education, and patients/public. Essential cross-level measures are multi-stakeholder communication and collaboration. Conclusion The implementation matrix resulting from this research helps to decompose the complexity of PBM implementation into concrete measures on each implementation level. It provides guidance for diverse stakeholders to design, initiate and develop strategies and plans to make PBM a national standard of care, thus closing current practice gaps and matching this unmet public health need.